2002
DOI: 10.1007/s00268-002-6515-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effect of Transdermal Glyceryl Trinitrate on Newly Constructed Arteriovenous Fistula

Abstract: Transdermal glyceryl trinitrate (GTN) administration may have a beneficial effect in the creation of an arteriovenous fistula (AVF) by increasing blood flow through the access and by inhibiting platelet aggregation. We evaluated the hemodynamic effects of transdermal GTN administration on newly constructed arteriovenous fistula. Radiocephalic fistula at the wrist (Brescia fistula) was constructed as the initial vascular access in 31 uremia patients (study = 16, control = 15). The patient demographics and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…10 Transdermal GTN has become a novel therapeutic in the treatment of several noncardiac conditions including patients with Raynaud's phenomenon, 13 Achilles tendinopathy 9 and newly constructed arteriovenous fistulas. 1 Furthermore, topical nitroglycerin has been successfully used in the treatment of peripheral ischemia in neonates. 11,15 Wong et al saw the reversal of peripheral tissue ischemia caused by indwelling radial artery catheterization and extravasation of dopamine using topical nitroglycerin ointment.…”
Section: Discussionmentioning
confidence: 99%
“…10 Transdermal GTN has become a novel therapeutic in the treatment of several noncardiac conditions including patients with Raynaud's phenomenon, 13 Achilles tendinopathy 9 and newly constructed arteriovenous fistulas. 1 Furthermore, topical nitroglycerin has been successfully used in the treatment of peripheral ischemia in neonates. 11,15 Wong et al saw the reversal of peripheral tissue ischemia caused by indwelling radial artery catheterization and extravasation of dopamine using topical nitroglycerin ointment.…”
Section: Discussionmentioning
confidence: 99%
“…AVF patency is affected by many factors, including but not limited to vessel diameter, patient age, and concomitant vascular disorders such as diabetes (10). Use of adjuvant medical therapies such as intraoperative heparin administration (11)(12), anti-platelet therapy (13)(14), topical glyceryl trinitrate injection (15), and postoperative flow monitoring (16) have been proposed as means of increasing patency rates, but not enough evidence currently exists to support their use, especially considering the costs and probable side effects, such as increased risk of bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…The application of GTN transdermal patches on to newly created AVFs is practised on an ad hoc basis, particularly where there are concerns about maturation. Little evidence supports this practice, although Akin and colleagues demonstrated that a locally applied GTN transdermal patch increased blood flow through the fistula after 24 h, and proposed that this application might improve maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Far‐infrared therapy has the potential to improve patency and maturation, with a proposed mechanism of stimulation of nitric oxide. In experimental settings locally applied nitrate (glyceryl trinitrate, GTN) therapy has also shown promise.…”
Section: Introductionmentioning
confidence: 99%